1988
DOI: 10.1172/jci113626
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of Escherichia coli heat stable enterotoxin in a human colonic cell line.

Abstract: Escherichia coli heat stable enterotoxin (ST.) caused Cl-secretion across T84 cell monolayers in a dose-dependent manner only when applied to the apical membrane surface and not when applied to the basolateral surface. Measurement of cAMP, cGMP, and free cytosolic Ca2l in response to STa suggested that cGMP alone mediated the Cl-secretory response. Studies utilizing blockers of the Na+,K+-ATPase pump, a Na+,K+,ClI cotransport system, a K+ channel, and a Cl-channel suggest that all of them participate in the Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
2
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 27 publications
(29 reference statements)
8
83
2
1
Order By: Relevance
“…The signals for short circuit current (Isc) and potential difference across the epithelium were measured every 20 sec, digitized with an ADC-1 data recording system (Remote Measurement Systems, Seattle) and stored for later analysis. The Isc observed with T84 cells cultured on permeable filters has been shown to be caused by the net secretion of chloride across T84 cell monolayers when cells were treated with various chloride secretogogues, including guanylin, uroguanylin, and Escherichia coli ST (1,2,15,26).…”
Section: Methodsmentioning
confidence: 99%
“…The signals for short circuit current (Isc) and potential difference across the epithelium were measured every 20 sec, digitized with an ADC-1 data recording system (Remote Measurement Systems, Seattle) and stored for later analysis. The Isc observed with T84 cells cultured on permeable filters has been shown to be caused by the net secretion of chloride across T84 cell monolayers when cells were treated with various chloride secretogogues, including guanylin, uroguanylin, and Escherichia coli ST (1,2,15,26).…”
Section: Methodsmentioning
confidence: 99%
“…We chose to test the acetylcholine analog carbachol since it was known that T84 cells respond to carbachol with a rise in intracellular calcium, an intracellular messenger which can potentiate the activation of protein kinase C. Huott et al had previously examined the cyclic GMP response of T84 cells to STavs STa plus carbachol for 15 min and did not note an increase in cyclic GMP with the addition of carbachol [5]. Based on our data, however, 15 min is too early to see an effect of carbachol ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The small peptide toxin STa, the heatstable toxin of E. coli, binds with high affinity to a receptor apparently distinct from particulate guanylate cyclase (GTP pyrophosphate lyase [cyclizing], EC 4.6.1.2) and stimulates the latter enzyme [2,3]. The T84 cell line is a human colon carcinoma cell line which responds to STa with a rise in cyclic GMP and to carbachol with a rise in intracellular calcium; both secretagogues result in chloride secretion [4][5][6][7]. Weikel et al recently showed that phorbol esters, which alone have no effect on cyclic GMP levels, enhanced STastimulated cyclic GMP levels by 1.6-2.4-fold [8].…”
Section: Introductionmentioning
confidence: 99%
“…Le site de phosphorylation serait la sérine en position 1029 du GC-C pour la PKC [25]. Ainsi, suite à l'attachement de STa, une production de GMPc est déclenchée, qui conduit à l'augmentation de la sécrétion intestinale de chlore et à l'inhibition de l'absorption de sodium [39,42,57,68,118] (pour illustration voir [33]). …”
Section: Activation De La Guanylate Cyclaseunclassified